The Effect of Loading Parameters and Dynamic Immersion Time on the Fatigue Life of Magnesium Bone Scaffolds - Risky Utama Putra; Nanda Yusril Mahendra; Dicky Pratama Putra; Akbar Teguh Prakoso; Hasan Basri; Hendri Chandra; Amir Putra Md Saad; Ardiyansyah Syahrom (International Conference on Science, Education, and Technology, 2023)
Bone scaffolding implants are used in orthopedic applications to aid bone growth and regeneration. However, these implants degrade over time and will also be exposed to the burden of physiological activity during use, which can affect their mechanical properties and fatigue life. The aim of this study was to investigate the effect of degradation time and physiological activity load on changes in bone scaffolding implant morphology on fatigue life and determine significant parameters using the ANOVA method. The study was conducted using numerical simulation using finite element method in software Comsol Multiphysics. Bone scaffolding implants are exposed to cyclic fatigue loads and degradation over time as well as loads of different physiological activities. The results showed that degradation time and physiological activity load had a significant effect on changes in bone scaffolding implant morphology and fatigue life. Increased degradation time and physiological activity load lead to decreased implant fatigue life. The results of the analysis using the ANOVA method showed that the degradation time of factors affecting fatigue with a percentage value of 64.56% was significant on morphological changes and the load of physiological activity had an influence of 35.44% on the fatigue life of bone scaffolding implants. This study emphasizes the importance of considering degradation time and physiological activity load in the design and evaluation of bone scaffold implants. Analysis using the ANOVA method can help to determine significant parameters that affect implant performance and improve implant design to extend fatigue life.